Bibliometric and visualized analysis on global trends and hotspots of TAK1 in regulated cell death: 1999 to 2024 - Huang, Kun; He, Ye; Wan, Hao; Ban, Xiao-Xia; Chen, Xin-Yu; Hu, Xi-Min; Wan, Xin-Xing; Lu, Rui; Zhang, Qi; Xiong, Kun (Frontiers in Immunology, 2024)
Background: Regulated cell death (RCD) is a genetically controlled form of cell death that plays an important role in organogenesis, tissue remodeling, and pathogenesis of cancers. Transforming growth factor-beta-activation kinase 1 (TAK1) is a member of the serine/threonine protein kinase family, which can respond to internal and external stimuli and participate in inflammatory responses through multiple signaling pathways and cellular processes. In the last two decades, the regulatory roles of TAK1 at the crossroads of multiple RCD pathways, including apoptosis, necroptosis, pyroptosis, and PANoptosis were revealed by 801 articles retrieved from the Web of Science Core Collection database. To analyze global research trends and hotspots concerning the role of TAK1 in RCD, the bibliometric and visualized analysis were applied in the current study. Methods: The data for this bibliometrics study were retrieved from the Web of Science Core Collection database. The search formula was (TS=(Apoptosis) OR TS=(pyroptosis) OR TS=(Necroptosis) OR TS=(PANoptosis) OR TS=(Autophagy) OR TS=(Ferroptosis) OR TS=(cuproptosis)) AND ((TS=(TAK1)) OR TS=(MAP3K7)). The co-occurrence and co-cited analysis on basic bibliometric parameters were conducted by VOSviewer. The dual-map overlay of journals, citation bursts, keyword timelines, and keyword bursts were analyzed by CiteSpace. Results: A total of 801 articles from 46 countries have been included in the analysis. The number of publications demonstrates a consistent increase from 1999 to 2024. The primary research institutions driving this field are Osaka University Notably, the Journal of Biological Chemistry stands out as the most popular journal in this domain. These publications collectively involve contributions from 4663 authors, with Jun Tsuji emerging as a prolific author. Jun Tsuji also gains the highest co-citation frequency. Emerging research hotspots are encapsulated by keywords, including apoptosis, NF-κB, inflammation, autophagy, and TNFα. Conclusion: This is the first bibliometric and visualized study to analyze the global trends and hotspots of TAK1 in RCD. Based on the analysis of 801 articles, the results provide a retrospective and comprehensive visualized view of the research hotspots and frontiers of TAK1 at the crossroads of multiple RCD signaling pathways and propose ideas for guiding their future investigations in molecular mechanisms and therapeutic strategies in this field.